The cyanogenic potential of cassava - Bokanga, M. (1994)
Manihot esculenta Cyanogenesis, the ability to produce hydrogen cyanide (HCN), is common to over 2000 plant species. In cassava, two cyanogenic glucosides, linamarin and lotaustralin, are produced in the leaves and stored inside vacuoles. Linamarase, an enzyme capable of hydrolyzing the glucosides, is also produced by the plant, but is stored in the cell wall. The hydrolysis of the glucosides and the release of HCN only occurs when plant tissues are damaged, e.g. during processing. Once produced, HCN evaporates. The term cyanogenic potential rather than HCN content should be used to express the concentration of cyanogenic glucosides and their breakdown products. Although the synthesis of linamarin and lotaustralin occurs only in the leaves, the two compounds are found in all plant tissues. There is no correlation between the cyanogenic potential of the roots and the cyanogenic potential of the leaves. There is a wide variation in the root cyanogenic potential. The variation is greater between roots of the same plant than between different plants of the same variety. A sampling scheme of 4 plants per plot in 4 replications is recommended when assessing the cyanogenic potential of a variety in field trials. Water stress increases the cyanogenic potential in cassava. The is a strong environmental effect on the expression of cassava's cyanogenic potential, but the genotype-environment interaction is very weak; Cyanides; Hydrocyanic acid; Germplasm; Africa; Latin AmericaManihot esculenta; Cianuros; Acido cianhídrico; Germoplasma; Africa; América LatinaCassava; Yuca; Fisiologíay bioquímica de la planta; Articles in proceedings; Artículos en memorias; Genética vegetaly fitomejoramiento Plant physiology and biochemistry; Plant genetics and breeding.